Identifying Deixis in Wonder Movie (2017) - Yuliana Dg. Macora; Riski Meilani (Sintuwu Maroso Journal of English Teaching, 2021)
This research purposed to find out the types of deixis in the movie titled Wonder and determine what is dominant deixis used. The object of the research is Auggie Pullman utterances. To identifying the types of deixis in Wonder, the researcher used the theory by Yule (1996) then determined what was the dominant deixis used in that film. This type of research is qualitative research. In collect the data, the researcher used script of Wonder movie (2017). The result of the research showed that the three types of deixis using theory of Yule (1996) such as person, time, and place deixis. The use of person deixis represented to Auggie and the participant in the movie. While, the time deixis represented to the timing of the conversation in the movie. Moreover, the place deixis represented to the distance of place or location from the conversation in the movie. The dominant deixis used is person deixis which is consist 254 deictic expressions from 285 data.